HAMLET: functional properties and therapeutic potential. (October 2012) - Ho CS, James; Rydström, Anna; Trulsson, Maria; Bålfors, Johannes; Storm, Petter; Puthia, Manoj; Nadeem, Aftab; Svanborg, Catharina
Human α-lactalbumin made lethal to tumor cells (HAMLET) is the first member in a new family of protein–lipid complexes that kills tumor cells with high selectivity. The protein component of HAMLET is α-lactalbumin, which in its native state acts as a substrate specifier in the lactose synthase complex, thereby defining a function essential for the survival of lactating mammals. In addition, α-lactalbumin acquires tumoricidal activity after partial unfolding and binding to oleic acid. The lipid cofactor serves the dual role as a stabilizer of the altered fold of the protein and a coactivator of specific steps in tumor cell death. HAMLET is broadly tumoricidal, suggesting that the complex identifies conserved death pathways suitable for targeting by novel therapies. Sensitivity to HAMLET is defined by oncogene expression including Ras and c-Myc and by glycolytic enzymes. Cellular targets are located in the cytoplasmic membrane, cytoskeleton, mitochondria, proteasomes, lysosomes and nuclei, and specific signaling pathways are rapidly activated, first by interactions of HAMLET with the cell membrane and subsequently after HAMLET internalization. Therapeutic effects of HAMLET have been demonstrated in human skin papillomas and bladder cancers, and HAMLET limits the progression of human glioblastomas, with no evidence of toxicity for normal brain or bladder tissue. These findings open up new avenues for cancer therapy and the understanding of conserved death responses in tumor cells.